Synthesis, characterization and electrochemical investigation of limn1.9ti0.1-xsnxo4 spinel cathode materials for lithium-ion batteries / Aida Fazliza Mat Fadzil - Mat Fadzil, Aida Fazliza (2020)
Spinel LiMn1.9Ti0.1O4 compound faces large capacity fading when the charge and discharge cycle is repeated. Due to this drawback, its structural and morphological properties as well as its electrochemical performance may be improved by doping. In this work, doping of LiMn1.9Ti0.1O4 with Tin (Sn) is done by using two methods which are the sol-gel method (SG) and self-propagation combustion method (SPC). The drive for this research is to obtain pure and single phase structure as well as optimising the annealing temperature. Thus, 700°C and 800°C were chosen. This study also focuses in improving the specific capacity and increase the capacity retention of batteries with these doped materials compared to LiMn1.9Ti0.1O4. Synthesizing using the SG method resulted in impurities of Mn2O3 and Mn3O4 for samples annealed at 700°C and 800°C, respectively. Contradicting, the SPC method gives a single and pure phase materials. Thus, the fundamental properties such as thermal behaviour and crystal structure, particle size, morphology and battery performance of samples synthesized by SPC method were studied in depth. The thermal properties of these materials were studied by Simultaneous Thermogravimetric Analysis (STA) to determine suitable annealing temperature for phase formation. The annealing temperature for LiMn1.9Ti0.1O4 with its doped materials, LiMn1.9Ti0.1-xSnxO4 (x = 0.001, 0.002, 0.003, 0.004 and 0.005) material were chosen based on the thermal profile of the samples. The phases for all the materials were studied by X-Ray Diffraction (XRD). XRD revealed that all samples annealed at 700 and 800 oC for 24 h showed pure and single phase. According to FESEM results, the morphologies obtained were polyhedral type crystal and the crystallite size increased as the ratio of Sn increases. EDX results showed that the calculated stoichiometry were in good agreement with the experimental errors of less than 15.0 %. The cyclic voltammetry (CV) results showed oxidation loop at potential more than 3.5 V. As such, doped LiMn1.9Ti0.1-xSnxO4 materials progress as good candidates for cathode materials. Of all the samples obtained, LiMn1.9Ti0.099Sn0.001O4 material has the best specific discharge capacity of 156.7 mAhg-1 in the first cycle, with capacity retention after 50th cycle of 69.0 %. Thus, LiMn1.9Ti0.099Sn0.001O4 material has potential as cathode material for use in lithium-ion batteries.